Preparação, caracterização e marcação de lipossomas pH - sensíveis com tecnécio-99m para identificação de focos inflamatórios - Vildete Aparecida Sousa Carmo (2007)
Physicochemical characterization of conventional and long-circulating pH-sensitive liposomes (DOPE/CHEMS and aPEG2000-DSPE or mPEG2000-DSPE/DOPE/CHEMS, respectively) as well as conventional and long-circulating non-pH-sensitive liposomes (DOPC/COL and aPEG2000-DSPE or mPEG2000-DSPE/DOPC/COL, or mPEG2000-DSPE/HSPC/COL, respectively) showed mean diameter vesicles between 99.8nm and 124,3nm, presenting good homogeneity (polydispersity index 0,25). The zeta potential was negative in all liposomes preparations, except in liposomes modified with aPEG2000-DSPE, which presented a positive zeta potential. Atomic force microscopy images showed that conventional pH-sensitive liposomes are prone to aggregation of vesicles. In vitro studies of the interaction of the complement system with the liposomes were performed using a hemolytic assay in rat serum. The nonpH- sensitive liposomes activated the complement system while pH-sensitiveliposomes shown to be poor activators of complement in rat serum. Studies of biodistribution and scintigraphic imaging were performed to evaluate the ability of long-circulating pH-sensitive liposomes composed of mPEG2000- DSPE/DOPE/CHEMS and labeled with technetium-99m (99mTc) to identify inflammatory and infectious sites in experimental models. Preformed glutathionecontaining long-circulating pH-sensitive liposomes were labeled with 99mTc- Hexamethylpropyleneamine oxime (99mTc-HMPAO). The radiolabeled long-circulating pH-sensitive liposomes (99mTc-SpHL) were administered intravenously afterinflammatory and infectious foci were induced in rats and mice, respectively. In the biodristribution studies, the animals were killed at pre-established time intervals, and tissues were removed and analyzed for 99mTc content using an automatic scintillation apparatus. Scintigraphic imaging was performed at different times after injection of99mTc-SpHL. A significantly amount of 99mTc-SpHL was taken up by organs of the mononuclear phagocyte system (spleen and liver). Moreover, the 99mTc-SpHL uptake was significantly higher in the inflamed and infected regions when compared to the respective controls (p<0.05), and the lesions could be visualized scintigraphically at30 minutes after injection. The ratio of the target/no-target radioactivity counts was superior to 1.5 at all times investigated. This result indicates that the 99mTc-SpHL presents a high tropism for inflammation and infection sites and may be useful as a radiopharmaceutical to identify these foci. Key words: pH-sensitive liposomes, technetium-99m, inflammation, infection, scintigraphy, complement system.